UJI SITOTOKSISITAS EKSTRAK DAUN MIMBA (Azadirachta indica) TERHADAP SEL FIBROBLAS BHK 21 - Qurni Restiani; Mandojo Rukmo; Devi Eka Juniarti (Conservative Dentistry Journal, 2017)
Background: The leaves of neem (Azadirachta indicia) is one of herbal medicine that recommended as an alternative material of root canal irrigants. The active ingredients of neem leaves such as alkaloids, tannins, saponins and flavonoids has been proven to have antibacterial activity against E. faecalis. The ideal properties of an alternative material of root canal irrigants is not only have antibacterial activity but also is not toxic to the tissues, but the toxicity of neem leaves remains unclear until now. Objective: The aims of this study to determine the toxicity effect of neem leaves extract in specific concentration. Methods: This research was an experimental laboratory in vitro study of baby hamster kidney fibroblast (BHK-21). The neem leaves extract was made by maceration method using ethanol 96% and certain dilution performed to obtain various concentrations. Cytotoxicity test was conducted by MTT assay and the optical density was measured using ELISA reader at wavelength of 620 nm. Then, the optical density values were calculated using the formula for determining the number of survival fibroblasts after tested. Results: The percentage of survival fibroblast at concentration of 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95, and 100% in sequence were 71.3%, 64, 2%, 62%, 60.2%, 40.1%, 36.3%, 36.7%, 29%, 28.4%, 27.5%, and 25.6% . Conclusion: The extract of neem leaves (Azadirachta indica) has cytotoxic effects at concentration of 70% up to 100%.